Development and Evaluation of Solid Lipid Nanoparticles for the Clearance of Aβ in Alzheimer's Disease - Meghana Goravinahalli Shivananjegowda; Umme Hani; Riyaz Ali M. Osmani; Ali H. Alamri; Mohammed Ghazwani; Yahya Alhamhoom; Mohamed Rahamathulla; Sathishbabu Paranthaman; Devegowda Vishakante Gowda; Ayesha Siddiqua (MDPI AG, 2023)
Aggregation of Amyloid-β (Aβ) leads to the formation and deposition of neurofibrillary tangles and plaques which is the main pathological hallmark of Alzheimer's disease (AD). The bioavailability of the drugs and their capability to cross the BBB plays a crucial role in the therapeutics of AD. The present study evaluates the Memantine Hydrochloride (MeHCl) and Tramiprosate (TMPS) loaded solid lipid nanoparticles (SLNs) for the clearance of Aβ on SHSY5Y cells in rat hippocampus. Molecular docking and in vitro Aβ fibrillation were used to ensure the binding of drugs to Aβ. The in vitro cell viability study showed that the M + T SLNs showed enhanced neuroprotection against SHSY5Y cells than the pure drugs (M + T PD) in presence of Aβ (80.35µM ± 0.455 µM) at a 3:1 molar ratio. The Box-Behnken Design (BBD) was employed to optimize the SLNs and the optimized M + T SLNs were further characterized by %drug entrapment efficiency (99.24 ± 3.24 of MeHCl and 89.99 ± 0.95 of TMPS), particle size (159.9 ± 0.569 nm), PDI (0.149 ± 0.08), Zeta potential (−6.4 ± 0.948 mV), Transmission Electron Microscopy (TEM), Atomic Force Microscopy (AFM) and in vitro drug release. The TEM & AFM analysis showed irregularly spherical morphology. In vitro release of SLNs was noted up to 48 h; whereas the pure drugs released completely within 3 hrs. M + T SLNs revealed an improved pharmacokinetic profile and a 4-fold increase in drug concentration in the brain when compared to the pure drug. Behavioral tests showed enhanced spatial memory and histological studies confirmed reduced Aβ plaques in rat hippocampus. Furthermore, the levels of Aβ decreased in AlCl3-induced AD. Thus, all these noted results established that the M + T SLNs provide enhanced neuroprotective effects when compared to pure and individual drugs and can be a promising therapeutic strategy for the management of AD.